Carbon source quality drives diazotroph community dynamics and life history strategies in agricultural soils - Chang Liu; Xuemei Hu; Yidan Jia; Haofei Zhang; He Sun; Shanshan Yang; Yajun Gao; Gehong Wei; Weimin Chen (Applied Soil Ecology, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Corrigendum to “Microbial diversity and residue quality interactively drive soil carbon priming via CAZyme regulation and necromass decomposition” [Appl. Soil Ecol. 218 (2026) 106671] - He Sun; Haofei Zhang; Chang Liu; Yiru Wang; Xuemei Hu; Siyuan Wang; Yajun Gao; Jiamin Xiao; Keke Jin; Likun Wu; Zhefei Li; Gehong Wei; et al. (Applied Soil Ecology, 2026)

Microbial diversity and residue quality interactively drive soil carbon priming via CAZyme regulation and necromass decomposition - He Sun; Haofei Zhang; Chang Liu; Yiru Wang; Xuemei Hu; Siyuan Wang; Yajun Gao; Jiamin Xiao; Keke Jin; Likun Wu; Zhefei Li; Gehong Wei; et al. (Applied Soil Ecology, 2026)

Long-term elevated CO2 and warming alter the network complexity and composition of bacterial community in a paddy field - Jiahui Li; Jiayi Xiong; Yexin Hu; Qingsong Ba; Feng Li; Fei Zhang; Li Jiang; Yuan Liu (Applied Soil Ecology, 2025)

Responses of complete and incomplete ammonia oxidizers to farmland reversion to forest in Ferralsols - Pengfei Zhang; Yongpeng Zhao; Lihua Ma; Shuling Wang; Min Yang; Alan L. Wright; Xianjun Jiang (Applied Soil Ecology, 2025)

Changes in soil microbial community and carbon use efficiency in freeze-thaw period restored after growth season under warming and straw return - Minghui Liu; Zhiming Zhang; Peng He; Yifei Zhang; Lu-Jun Li (Applied Soil Ecology, 2025)